Studi Perbandingan Pengaruh Variasi Bentuk Lengkung terhadap Stabilitas Struktur Jembatan Pelengkung: Studi Kasus Model Kompetisi Jembatan Indonesia XIX Tahun 2024 - Bestari, Legat; Priskasari, Ester; Sunarwadi, Hadi Surya Wibawanto (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2025)
Arch bridges represent a widely favoured structural form, celebrated for their inherent efficiency and aesthetic appeal. Variations in arch geometry, such as circular and parabolic shapes, exert a significant influence on both the structural stability and load distribution within the design. This research endeavours to conduct a comparative analysis of how distinct arch geometries—specifically circular and parabolic—impact the structural stability of arch bridges. The investigation centres on a case study utilising a model arch bridge from the 19th Indonesian Bridge Competition (KJI) in 2024. The methodology employed involves structural analysis facilitated by SAP2000 v.24 software, adhering strictly to the guidelines set forth by KJI XIX 2024 and SNI 1729:2020 for comprehensive evaluation. Key parameters subjected to analysis included internal forces, stress, strain, deflection, and material efficiency. The analytical findings reveal that the bridge model incorporating a parabolic arch demonstrates superior performance. While the maximum axial forces in the arch rib and hangers were higher in the parabolic model, this model exhibited substantially lower bending moments in the arch rib (45.36 kNmm) and longitudinal girder (32.55 kNmm) when compared to the circular arch model (86.51 kNmm and 87.41 kNmm). Furthermore, the maximum deflection observed in the parabolic model (1.75 mm) was notably less than that of the circular model (2.21 mm). In terms of material consumption, the parabolic arch bridge model proved more efficient, with a total weight of 19.19 kg, making it 51.9% lighter than the circular arch bridge model, which weighed 37 kg. In conclusion, the parabolic arch form imparts enhanced structural stability and greater material efficiency, proving more effective in channelling loads primarily into pure compressive forces, thereby mitigating overall bending moments and deformations.